Draft genome sequence of streptococcus agalactiae TA B490, a multidrug-resistant strain isolated from bovine mastitis in Argentina - Cadona, Jimena Soledad (2021)
Streptococcus agalactiae is a bovine pathogen that causes intramammary infections. For humans, S. agalactiae is a leading cause of neonatal death and an emerging pathogen in adults. Here, we present the draft genome sequence of S. agalactiae TA B490, a multidrug-resistant strain isolated from bovine mastitis in Argentina.